Milk Thistle and Its Derivative Compounds: A Review of Opportunities for Treatment of Liver Disease. (9th November 2012) - Hackett, E.S.; Twedt, D.C.; Gustafson, D.L.
Abstract : Milk thistle extracts have been used as a "liver tonic" for centuries. In recent years, silibinin, the active ingredient in milk thistle extracts, has been studied both in vitro and in vivo to evaluate the beneficial effects in hepatic disease. Silibinin increases antioxidant concentrations and improves outcomes in hepatic diseases resulting from oxidant injury. Silibinin treatment has been associated with protection against hepatic toxins, and also has resulted in decreased hepatic inflammation and fibrosis. Limited information currently is available regarding silibinin use in veterinary medicine. Future study is justified to evaluate dose, kinetics, and treatment effects in domestic animals.